A Business Model Of Marketing Capabilities And Marketing Performances -The Case Of Micro-Enterprises (MiEs) In Kedah - Mohamed, Baderisang (2009)

(untitled)
This need for a marketing capabilities model that is applicable to MiEs underlies the principal purpose of this research to identify what are the marketing capabilities applied in MIEs.Keperluan untuk model keupayaan pemasaran yang berkaitan dengan enterprais mikro (MiEs) merupakan sebab utama tujuan penyelidikan ini untuk mengenal pasti apakah keupayaan pemasaran yang diguna pakai oleh MiEs;